Direct visualisation of internalization of the adenosine A3 receptor and localization with arrestin3 using a fluorescent agonist - Stoddart, Leigh A.; Vernall, Andrea J.; Briddon, Stephen J.; Kellam, Barrie; Hill, Stephen J. (Elsevier, 2015)
Fluorescence based probes provide a novel way to study the dynamic internalization process of G protein-coupled receptors (GPCRs). Recent advances in the rational design of fluorescent ligands for GPCRs have been used here to generate new fluorescent agonists containing tripeptide linkers for the adenosine A3 receptor. The fluorescent agonist BY630-X-(D)-A-(D)-A-G-ABEA was found to be a highly potent agonist at the adenosine A3 receptor in both reporter gene (pEC50 = 8.48 ± 0.09) and internalization assays (pEC50 = 7.47 ± 0.11). Confocal imaging studies showed that BY630-X-(D)-A-(D)-A-G-ABEA was internalized with A3 linked to yellow fluorescent protein, which was blocked by the competitive antagonist MRS1220. Internalization of untagged adenosine A3 could also be visualized with BY630-X-(D)-A-(D)-A-G-ABEA treatment. Further, BY630-X-(D)-A-(D)-A-G-ABEA stimulated the formation of receptor–arrestin3 complexes and was found to localize with these intracellular complexes. This highly potent agonist with excellent imaging properties should be a valuable tool to study receptor internalization.